Regulation of human UDP-glycosyltransferase (UGT) genes by miRNAs. (3rd April 2022) - Hu, Dong Gui; Mackenzie, Peter I.; Hulin, Julie-Ann; McKinnon, Ross A.; Meech, Robyn
Abstract: The human UGT gene superfamily is divided into four subfamilies ( UGT1, UGT2, UGT3 and UGT8 ) that encodes 22 functional enzymes. UGTs are critical for the metabolism and clearance of numerous endogenous and exogenous compounds, including steroid hormones, bile acids, bilirubin, fatty acids, carcinogens, and therapeutic drugs. Therefore, the expression and activities of UGTs are tightly regulated by multiple processes at the transcriptional, post-transcriptional and post-translational levels. During recent years, nearly twenty studies have investigated the post-transcriptional regulation of UGT genes by miRNAs using human cancer cell lines (predominantly liver cancer). Overall, 14 of the 22 UGT mRNAs (1A1, 1A3, 1A4, 1A6, 1A8, 1A9, 1A10, 2A1, 2B4, 2B7, 2B10, 2B15, 2B17, UGT8) have been shown to be regulated by various miRNAs through binding to their respective 3′ untranslated regions (3′UTRs). Three 3′UTRs (UGT1A, UGT2B7 and UGT2B15) contain the largest number of functional miRNA target sites; in particular, the UGT1A 3′UTR contains binding sites for 12 miRNAs (548d-5p, 183-5p, 214-5p, 486-3p, 200a-3p, 491-3p, 141-3p, 298, 103b, 376b-3p, 21-3p, 1286). Although all nine UGT1A family members have the same 3′UTR, these miRNA target sites appear to be functional in an isoform-specific and cellular context-dependent manner. Collectively, these observations demonstrate that miRNAs represent important post-transcriptional regulators of the UGT gene superfamily. In this article, we present a comprehensive review of reported UGT/miRNA regulation studies, describe polymorphisms within functional miRNA target sites that may affect their functionalities, and discuss potential cooperative and competitive regulation of UGT mRNAs by miRNAs through adjacently located miRNA target sites.